Dielectric performance analysis of laboratory aged power cable under harmonic voltages - Uydur, Cihat Cagdas; Arikan, Oktay (SPRINGER, 2022)
In recent years, due to the increasing use of nonlinear loads, the level of harmonics deteriorating the power quality has also increased in the distribution system. The harmonics have a negative effect on the behavior of equipment and materials, as they distort voltage and current waveforms of the system it is connected to. This leads to heating problems due to additional losses for the distribution system components. Due to the multitude of technical, environmental and social causes, the use of power cables, especially cross-linked polyethylene (XLPE) power cables, is increasing rapidly. In this context the problem of power system harmonics and using of XLPE power cables in distribution systems are spreading simultaneously. In this study, 60 kV overvoltage (5 center dot U-0) aging process was performed on 12/20.8 kV XLPE power cable samples at Yildiz Technical University High Voltage Laboratory. The dielectric parameters (P-K, tan delta and C) of the aged cable samples were measured. By using OMICRON CPC100/CP-TD1 measuring device, the effects of harmonics with different measurement voltages have been examined on underground cables. The performance of aged cables is analyzed under harmonic voltages and the results are presented. The disruptive effects created by the 3rd-5th and 7th order harmonics have been revealed.
Keywords: Aging; Dissipation factor; Total harmonic distortion; XLPE cables; XLPE CABLE; HIGH-FREQUENCY; INSULATION; TEMPERATURE; BREAKDOWN; Engineering